2018
DOI: 10.1002/asia.201800120
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Synthesis of Isoindolinone Frameworks via RhIII‐Catalysed in situ Directing Group‐Assisted Tandem Oxidative Olefination/Michael Addition

Abstract: A Rh -catalysed three-component synthesis of isoindolinone frameworks via direct assembly of benzoyl chlorides, o-aminophenols and activated alkenes has been developed. The process involves in situ generation of o-aminophenol (OAP)-based bidentate directing group (DG), Rh -catalysed tandem ortho C-H olefination and subsequent cyclization via aza-Michael addition. This protocol exhibits good chemoselectivity and functional group tolerance. Computational studies showed that the presence of hydroxyl group on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Using Pd(TFA) 2 and PdCl 2 in parallel experiment gave inferior results, respectively (entries 4-5, Table 1). Subsequently, varying the additive species to AgOAc, KIO 3 and Cu(OAc) 2 suggested that KIO 3 was amongst the most favourable additive (entries 6-8, Table 1). Increasing the loading of additive did not improve the reaction (entry 9, Table 1), and decreasing the amount of base led to reduced yield of 3 a (entry 10, Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Pd(TFA) 2 and PdCl 2 in parallel experiment gave inferior results, respectively (entries 4-5, Table 1). Subsequently, varying the additive species to AgOAc, KIO 3 and Cu(OAc) 2 suggested that KIO 3 was amongst the most favourable additive (entries 6-8, Table 1). Increasing the loading of additive did not improve the reaction (entry 9, Table 1), and decreasing the amount of base led to reduced yield of 3 a (entry 10, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…[2] Later on, this DG was found as effective fragment in assisting the tandem CÀ H olefination and intramolecular hydroamination for the synthesis of isoindolinones with Rh-/Cu-cocatalyst system. [3] Rather recently, Panda and Sahoo developed the tandem synthesis of alkenyl functionalized benzoxazoles via a key CÀ H alkenylation with palladium catalysis using OAP-functionalized benzamides. [4] In despite of these inspiring works, more different CÀ H bond activation reactions assisted by such DGs are yet to explore.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Zhang and co‐workers successfully demonstrated a one‐pot multi‐component synthesis of isoindolinones via C−H olefination from readily available starting materials such as benzaldehydes, aryl amines and activated olefins using [Cp * RhCl 2 ] 2 as catalyst ( Scheme ) . In the same year, a similar work was carried out by Wang an co‐workers using benzoyl chlorides, o ‐amino phenol and activated olefins using the same catalyst for the synthesis of isoindoline frameworks ( Scheme ) …”
Section: Rhodium‐catalysed Multi‐component Reactionsmentioning
confidence: 97%
“…Rh III -catalyzed three-component synthesis of isoindolinone frameworks was achieved by both Wang et al [50] and Zhang et al [51] Wang used ac ombination of benzoyl chloride derivative, 2-aminophenol and electron deficienta lkene derivatives to synthesize av ariety of substituted isoindolinones in as ingle step under air (Scheme 14 A). In comparison, Zhang utilized an aromatica ldehyde, 2-aminopyridines and similarly activated olefins under nitrogen atmosphere,a nd was able to synthesize pagoclone andp azinaclone in as ingle step, albeit in 15 %a nd 20 %i solated yields, respectively (Scheme 14 B).…”
Section: Rh-catalyzed Olefination/alkylation-cyclizationmentioning
confidence: 99%
“…Rh III ‐catalyzed three‐component synthesis of isoindolinone frameworks was achieved by both Wang et al [50] . and Zhang et al [51] .…”
Section: C−h Functionalization: Annulation/cyclizationmentioning
confidence: 99%